Leo Strauss and the politics of American empire - Norton, Anne (Yale University Press, 2004)
The teachings of political theorist Leo Strauss (1899-1973) have recently received new attention, as political observers have become aware of the influence Strauss's students have had in shaping conservative agendas of the Bush administration - including the war on Iraq. This provocative book examines Strauss's ideas and the ways in which they have been appropriated, or misappropriated, by senior policymakers. Anne Norton, a political theorist trained by some of Strauss's most famous students, is well equipped to write on Strauss and Straussians. She tells three interwoven narratives: the story of Leo Strauss, a Jewish German-born emigre, who carried European philosophy into a new world; the story of the philosophic lineage that came from Leo Strauss; and the story of how America has been made a moral battleground by the likes of Paul Wolfowitz, Leon Kass, Carnes Lord, and Irving Kristol - Straussian conservatives committed to an American imperialism they believe will usher in a new world order.